The use of an electronic portfolio for increasing writing skills to tenth grade at EBG José Pedro Varela, La Libertad, province of Santa Elena, 2015-2016. - Barzola Tigrero, Jazmine (2016)
In the present days, the use of information and communication technologies (ICTS) has emerged in our society due to the globalization. Big changes have been developed thanks to the use of technology especially in medicine and education field. Technology and education are closely connected because educators had implemented new strategies with the use of ICT, these tools allow students to acquire knowledge, develop skills, and create their own knowledge looking for new methodological resources using internet. The use of an electronic portfolio let students to develop the necessary skills in the teaching and learning process with the supervising of teachers in their role of guides. The present research shows the improvement of English writing skills work of the tenth grade students at Escuela de Educación Básica José Pedro Varela through the implementation of an electronic portfolio. The fundamental base of this research is to help students in their academic performance, the research is also based in the opinions and theories of important authors that used technology in education, as Jeremy Harmer, Bartholomae, Hyland, Margarita Garrido and others. To carry out the research project was necessary to select different methods and also techniques as surveys and interviews to obtain the highest level of accuracy and reliability. Portfolios are a collection of work used for some purposes, in education field nowadays it is common to use portfolios to collect information and activities given in the academic year with the purpose of reviewing and reinforcing knowledge. The uses of electronic portfolios will benefit students with low academic performance through the constant practice of activities given in the cuadernia application.